BACTERIAL (SEPTIC) ARTHRITIS AND INFECTION OF A PROSTHESIZED JOINT: CURRENT ASPECTS - B S Belov (Современная ревматология, 2010)
The paper gives an update on the etiology, pathogenesis, clinical picture, diagnosis, and treatment of bacterial arthritis and infection of a prosthesized joint.